PENERAPAN METODE PEMBELAJARAN DISKUSI DENGAN TEKNIK MIND MAPPING (PETA KONSEP) DALAM MENUMBUHKAN MINAT BELAJAR SISWA KELAS IX SMPN. 1 MANGARABOMBANG - Rifdan Rifdan; Imam Suyitno; Retno Astuti Dwi Anjani Muhajir (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2022)
Research Objectuves: (1) the implementation of learning with using the Mind Mapping discussion method (concept maps) to foster interest student learning grade IX.G SMP Negeri 1 Mangarabombang Takalar (2) Is it in the process of using the discussion learning method using the Mind Mapping technique (concept map) there are obstacles faced in its application. This research is a qualitative research. The types and sources of data used in this study are primary data sources and secondary data sources. Data collection techniques through observation, application of methods, interviews and documentation. The results showed that: (1) The implementation of learning by using the Mind Mapping discussion method (concept map) can foster interest in learning for class IX.G students at SMP Negeri 1 Mangarabombang Takalar and has given a good impact by fostering student interest in learning, because students are more happy with the discussion learning method with mind mapping techniques (concept maps). The application of discussion learning carried out with direction and guidance by the teacher can form student interest in learning, students train creativity in thinking with Mind Mapping. (2) There are several supporting factors in the successful application of the discussion learning method with mind mapping techniques (concept maps), including, (a) factors from the teacher, the teaching ability of a teacher can stimulate the thinking process and help the growth of critical attitudes of students. ; (b) factors from students, with this method students are more confident in expressing their opinions, students become more familiar with their teachers because discussions open up attachments so that everyone is free with their opinions, students become high in enthusiasm in studying the material; (c) factors from the environment. The environment that affects the learning process in the classroom and the environment around the school, in the classroom such as clean classroom conditions while factors from the school environment such as the availability of guaranteed facilities and infrastructure in the implementation of the learning method process